A Brief Review on Fuzzy Logic Used in Vehicle Dynamics Control - Uzunsoy, Erdem (Bursa Teknik Üniversitesi, 2018)
As an implication of a mathematical set theory, fuzzy logic has widely been used in engineering applications, since its invention. One of the popular areas, which the logic could successfully penetrate the real world, is the automotive engineering. Especially; rulemaking authorities, a competitive sector and more conscious customers challenge the vehicle designers to use state of the art technologies for better performance, safety and higher dynamic requirements. Therefore, although the style design has been an attraction point in the first place, nowadays, control systems have been the distinguishing parameter of the vehicle design. Certainly, not only the hardware used for the control, but also the method used is important in judgement of the system’s success. Fuzzy logic control (FLC) has been studied and applied in vehicle dynamics control model and the systems for decades. The method is classified in the intelligent control systems and is capable of dealing with the systems consisting of uncertainty and non-linearity as in some fields of automotive engineering. From this point of view, this paper aims to reveal the most commonly used FLC applications in vehicle dynamics literature.